STUDI TENTANG PENGETAHUAN SIKAP DAN PERILAKU PENDERITA INFEKSI SALURAN PERNAPASAN AKUT (ISPA) DI WILAYAH KERJA UPTD PUSKESMAS BANJARMANGU 2 - Barni; Seli Puji Rahayu (Jurnal Ilmiah Medsains, 2022)
ARI is still a public health problem today. Puskesmas Banjarmangu 2 is one of the Puskesmas in Banjarnegara Regency which still has ARI disease problems. Based on observations from January to March 2022, the prevalence of ARI is still quite high. The purpose of this study was to find out and describe the description of knowledge, attitudes and behavior as well as the physical condition of the house of patients with ARI (Acute Respiratory Infection) in the Work Area of ​​the Banjarmangu Health Center 2. This study was included in a descriptive study with a cross sectional method. The population in this study were patients with ARI Puskesmas Banjarmangu 2 who had checked themselves at the Puskesmas in the period March 2022, namely 58 people with random sampling technique. The data used in this study are primary data obtained from questionnaires and field observations as well as secondary data from previous studies. Data analysis was carried out in a univariate way. The results showed that the patient's knowledge level was good (67.2%), the patient's attitude was good (93.1%), and the patient's behavior was good (87.9%).